2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic variation on the dynamics of neurodegeneration in Alzheimer's disease

Abstract: Although many genetic markers are identified as being associated with Alzheimer's disease (AD), not much is known about their association with the structural changes that happen as the disease progresses. In this study, we investigate the genetic etiology of neurodegeneration in AD by associating genetic markers with atrophy profiles obtained using patient data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort. The atrophy profiles were quantified using a linear least-squares regression model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The LRRN3 gene has also recently been linked with differential gene expression by age after traumatic brain injury (TBI) (Cho et al, 2016). Lastly, the Sortilin Related VPS10 Domain Containing Receptor 1 ( SORCS1 ) is a protein-coding gene that is also associated with a brain disorder, however unlike LRRN3 it is not TBI but narcolepsy and neurodegeneration in Alzheimer's (Knight et al, 2016; Printy, Verma, Cowperthwaite, Markey, & Alzheimer's Disease Neuroimaging Initiative, 2014; Scheinfeldt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The LRRN3 gene has also recently been linked with differential gene expression by age after traumatic brain injury (TBI) (Cho et al, 2016). Lastly, the Sortilin Related VPS10 Domain Containing Receptor 1 ( SORCS1 ) is a protein-coding gene that is also associated with a brain disorder, however unlike LRRN3 it is not TBI but narcolepsy and neurodegeneration in Alzheimer's (Knight et al, 2016; Printy, Verma, Cowperthwaite, Markey, & Alzheimer's Disease Neuroimaging Initiative, 2014; Scheinfeldt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have demonstrated links between SNPs in SORCS1 and cognition. Printy et al [ 49 ] assessed atrophy profiles against genetic markers in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort, finding associations of cerebral atrophy with SNPs on APP but also ventricular enlargement with SNPs on SORCS1 . Reitz et al [ 53 ] also assessed the impact of genetic variation in SORCS1 and memory retention and found three SNPS were associated with memory retention.…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant synergistic interaction between two SNPs in an olfactory gene cluster suggested that this pathway may be involved in AD. Using a subset of imaging features able to discriminate between CN and AD subjects as quantitative phenotypes, genetic variation in a relatively small number of genes ( ESR1 , BIN1 , LDLR , SORCS1 , APP , LRAT , and TF ) was found to be associated with ventricular enlargement, hippocampal atrophy, and cortical atrophy, suggesting that these loci could have potential in diagnostic classification [213]. Another study selected neuroimaging biomarkers associated with disease state on the basis of global shape analysis and found differential associations between SNPs and regional volumes at different disease stages [214].…”
Section: Studies Of Genetic Associationsmentioning
confidence: 99%